2016
DOI: 10.5114/pr.2016.61533
|View full text |Cite
|
Sign up to set email alerts
|

A consensus statement – part I. Recommendations for the management of chronic venous disease (CVD) in India and the key role of primary care doctors

Abstract: What does the term "chronic venous disease" cover? The term "chronic venous disease" (CVD) covers a full spectrum of venous conditions of lower limbs, ranging from patients with early symptoms, like telangiectasia (reticular veins), leg pain, or oedema of the foot, to complications like venous leg ulcers. In the early stages usually only symptoms appear, then as the disease progresses it is accompanied by signs. Venous symptoms are defined as tingling, aching, burning sensation, muscle cramps, swelling, sensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(24 reference statements)
0
8
0
1
Order By: Relevance
“…Leg elevation for 1 h/day was significantly associated with prevention of venous ulcer recurrence and 45% increase of the laser Doppler flux (i.e., flow within veins) [26,27]. In accordance with this evidence, several guidelines recommend leg elevation in the management of venous ulcers [1,6,11,28].…”
Section: Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Leg elevation for 1 h/day was significantly associated with prevention of venous ulcer recurrence and 45% increase of the laser Doppler flux (i.e., flow within veins) [26,27]. In accordance with this evidence, several guidelines recommend leg elevation in the management of venous ulcers [1,6,11,28].…”
Section: Recommendationsmentioning
confidence: 99%
“…Their incidence increases with age and female sex [2][3][4]. A large Indian study revealed that CVD is more prevalent at an average age of 43 years and it affects women more than men [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic venous disease of the lower limbs is one of the major problems observed in vascular surgery practice; however, it remains an underdiagnosed condition in general clinical practice because of many factors which can broadly be divided as patient- and healthcare provider-related factors. Patients usually neglect the disease till it impairs the quality of life or limits the overall functioning of lower extremity 1 . Primary care physicians often tend to ignore or overlook the problem because of the underappreciation of the consequences 2 .…”
mentioning
confidence: 99%